Design and characterisation of dual‐mode suspended‐substrate stripline filter. Issue 9 (30th April 2018) - Binti Mohd Najib, Norazwana; Somjit, Nutapong; Hunter, Ian
Abstract : A new design technique of a dual‐mode ring‐resonator suspended‐substrate stripline filter is reported here to achieve low passband insertion loss, high quality factor, and good spurious response. A fourth‐order bandpass filter was designed and fabricated at the operational frequency of 2.07 GHz with two ring resonators packaged in a metallic cavity where each ring resonator is one wavelength long. The transmission zeros of the dual‐mode filter are generated due to the phase cancellation between the two paths in a ring, thus a sharp‐skirt selectivity filter response was achieved. Perturbation notch structure was implemented on each ring resonator to provide the electromagnetic coupling of two degenerate modes, thus a dual‐mode response of the filter can be synthesised. Measurement results of the first dual‐mode filter prototype showed a return loss and an insertion loss of better than 16.42 and 0.926 dB, respectively, while an out‐of‐band rejection of up to 55 dB was achieved. The novel filter design technique proved that no cross‐coupling is required to obtain the transmission zeros of the filter, thus the sharp‐skirt response was achievable.